Low-phosphorus chemical nickel solution and application thereof
By using adipic acid and glutaric acid as complexing agents in low-phosphorus chemical nickel solution and adding polysulfide compound LP to adjust the pH value, the problems of fluctuations in the low-phosphorus chemical nickel plating layer and slow reaction speed are solved, and a low-phosphorus plating layer with high stability and good electromagnetic properties are achieved.
Patent Information
- Application Number
- CN202411893177.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art has problems such as fluctuation in the low-phosphorus electroless nickel plating layer, slow reaction speed and insufficient tolerance to nickel phosphite. Especially in the electroplating process of flexible materials, the coating uniformity and poor electromagnetic performance.
Adipate, glutaric acid or their salts are used as complexing agents, and the polysulfide compound LP is added to the chemical nickel solution to adjust the pH value to 4.0-5.4 to obtain a low-phosphorus plating layer and improve the stability and uniformity of the plating layer.
It is possible to obtain a low phosphorus content plating layer under low pH conditions, avoid the problem of complexing agent polymerization at high temperatures, improve the stability and reaction speed of the plating solution, the service life of the plating layer exceeds 15 cycles, and has good electromagnetic properties.
Abstract
Description
Technical Field
[0001] The invention relates to a chemical nickel solution, in particular to a low-phosphorus chemical nickel solution and application thereof. Background Art
[0002] Chemical nickel plating has certain decorative properties, good corrosion resistance, and good wear resistance after heat treatment. At the same time, the chemical nickel process has excellent plating uniformity, so it has been widely used in industries such as automobiles, electronics, chemicals, textiles, printing, and various mechanical equipment. Nickel-phosphorus alloy plating with a phosphorus content of less than 4% is a low-phosphorus plating. The structure of low-phosphorus chemical nickel plating is different from that of medium- and high-phosphorus plating. It is a crystalline structure with good brazing ability, magnetism, strong wear resistance, and good corrosion resistance in alkaline environments. It has great application potential in industries such as electronics, chemicals, and metallization of flexible materials.
[0003] There are many studies on low-phosphorus chemical nickel, such as "Study on the process of chemical plating low-phosphorus nickel-phosphorus alloy" published by Liu Qiong and others from the Department of Applied Chemistry of Harbin Institute of Technology, in which low-phosphorus Ni-P alloy was chemically plated at pH 6 using a propionic acid-lactic acid system (Liu Qiong, Li Ning, Wu Yongming, Electroplating and Finishing, Issue 4, 2008); "Composition and structure of low-phosphorus chemical nickel plating layer" published by Fang Jingli and others from the Institute of Applied Chemistry of Nanjing University, which involves obtaining low-phosphorus chemical nickel under alkaline conditions (Fang Jingli, Ye Xiangrong, Fang Jing, Applied Chemistry, Issue 5, 1992). In the prior art, low-phosphorus chemical nickel is generally obtained at a pH of 6 or above. High pH is prone to produce nickel phosphite precipitation, requiring more efficient complexing agents for complexation. Temperature and pH have a great influence on phosphorus content. The higher the relative pH, the lower the phosphorus content. The lower the pH and temperature, the slower the reaction rate. How to balance the reaction rate and the tolerance of nickel phosphite is also a technical problem that needs to be solved in the prior art. Chinese patent CN 118390030 A discloses a surface treatment process for aluminum alloys, wherein the low-phosphorus nickel plating solution involved is: 20 g / L nickel sulfate, 25 g / L sodium hypophosphite, 15 g / L sodium acetate, 25 g / L sodium hydroxyacetate and 1.5 mg / L stabilizer Pb 2+The pH value of the mixed solution is 4.5. Although the pH value can be reduced to below 6, it is necessary to use hydroxycarboxylic acid compounds as complexing agents. Hydroxycarboxylic acid compounds are easy to polymerize at high temperatures, affecting the complexing performance and increasing the viscosity of the solution. In addition, the phosphorus content of low-phosphorus chemical nickel with hydroxycarboxylic acid complexing agents will also increase with the increase of cycles. For example, Zheng Zhen of Harbin Institute of Technology published a study on the screening and supplementary process of low-phosphorus chemical nickel plating stabilizers in 2008, using lactic acid and propionic acid as complexing agents. Table 2-4 (Changes in coating properties during periodic tests) shows that the phosphorus content in the first cycle is 2.9%, and the phosphorus content is greater than 4% from the second cycle. Greater than 4% does not belong to the true low-phosphorus category, and the use cycle has a significant impact on the use cost. The use cost of 10 cycles is less than 1 / 5 of the use cost of one cycle, and the amount of scrapped wastewater is 1 / 5. Therefore, the phosphorus content problem of low-phosphorus chemical nickel solution needs to be solved in terms of periodicity.
[0004] Flexible materials, especially conductive fabrics, have metallic properties and the softness of fabrics, and are easy to process. As electromagnetic shielding materials, they are increasingly used in mobile phones, new energy vehicles and other electronic devices, and have developed rapidly in recent years. The current conventional practices for metallization of flexible materials include: 1. Vacuum PVD nickel plating and then electroplating metal thickening, 2. Colloidal palladium activation-degumming-low temperature alkaline chemical nickel and then electroplating metal thickening. At present, whether it is vacuum nickel plating or alkaline chemical nickel plating, the thickness of the coating is a few microns, which cannot meet the requirements of electroplating thickening for electromagnetic performance. Flexible materials, especially conductive fabrics, have a large surface, and the current distribution is uneven during electroplating, resulting in poor uniformity of the metal layer of the material after metallization, affecting the use effect. When flexible materials (conductive fabrics) use the colloidal palladium activation-degumming-low temperature alkaline chemical nickel process, due to the large surface area of the material, continuous alkaline chemical nickel plating is easy to cause chemical nickel decomposition, and it is urgent to develop a new method to meet the actual needs of production. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention proposes a low-phosphorus chemical nickel solution and its application which can better meet the actual production needs.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is: A low-phosphorus chemical nickel solution comprises the following components: 10-40 g / L of a nickel ion source, 5-50 g / L of a complexing agent, 5-40 g / L of sodium hypophosphite, and 2-30 ppm of a polysulfide compound LP, wherein the complexing agent is one or more of adipic acid, adipic acid salt, glutaric acid, and glutaric acid salt.
[0007] The present invention uses adipic acid, glutaric acid or their salts as complexing agents to obtain a coating with a lower phosphorus content. If a polysulfide compound LP is added at the same time, a low-phosphorus coating can be obtained. We found that the addition of a mature market product, polysulfide compound LP, used as a grain refiner and brightener in copper plating additives to chemical nickel solution has a relatively large impact on the phosphorus content of the chemical nickel coating, and can reduce the phosphorus content of the coating by 1-2%. In the chemical nickel plating solution, LP combined with adipic acid or adipic acid salt, glutaric acid or glutaric acid salt or a combination thereof as a complexing agent can effectively reduce the phosphorus content of the coating to less than 4%, and obtain a low-phosphorus chemical nickel coating with strong stability and no pinhole phenomenon, a service life of more than 15 cycles, and a fast reaction speed.
[0008] Preferably, taking into account both the reaction speed and the tolerance of nickel phosphite, the pH of the low-phosphorus chemical nickel solution is adjusted to 4.0-5.4 for standby use.
[0009] Preferably, the nickel ion source is nickel sulfate, nickel sulfamate or nickel chloride.
[0010] Preferably, the components of the low-phosphorus chemical nickel solution also include one or more of a buffer, a stabilizer, and a brightener.
[0011] Preferably, the buffer comprises boric acid; the stabilizer comprises one or more of iodates, iodized salts, antimony compounds, thioureas, and lead compounds; and the brightener comprises one or more of water-soluble unsaturated organic matter, bismuth compounds, and cadmium compounds.
[0012] The present invention also provides an application of the low-phosphorus chemical nickel solution. Under a pH value of 4.0 to 5.4, the pretreated substrate is placed in the low-phosphorus chemical nickel solution for electroplating. The plating temperature is 70 to 80° C., and the phosphorus content of the obtained coating is less than 4%.
[0013] Preferably, the plating time is 2 to 30 minutes.
[0014] Preferably, the service life of the low-phosphorus chemical nickel solution is more than 15 cycles.
[0015] Preferably, the substrate comprises an iron substrate, a copper substrate and a flexible material.
[0016] Preferably, the low-phosphorus chemical nickel solution is used to prepare conductive cloth.
[0017] Compared with the prior art, the beneficial effects and advantages of the present invention are: (1) The present invention can obtain a coating with a lower phosphorus content under a lower pH value, and can avoid the problem of lipid polymerization at high temperature in a complexing agent system containing both hydroxyl and carboxylic acid groups, thereby improving the stability of the plating solution. The present invention can obtain a low-phosphorus chemical nickel coating under milder conditions, which has strong stability and no pinhole phenomenon, a service life of more than 15 cycles, and a faster reaction speed; (2) The low-phosphorus chemical nickel solution of the present invention has the characteristics of high stability and high speed. In particular, the low-phosphorus chemical nickel has excellent electromagnetic properties and can replace low-temperature chemical nickel and electroplating thickening processes, making the production of flexible materials more convenient and the coating uniformity better; it meets the requirements of flexible materials for good conductivity (<0.5Ω / in) and electromagnetic wave shielding effect (the shielding range can be between 100K and 3GHz). The flexible material conductive cloth of the present invention is flexible. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention is further specifically described below through examples, which are provided for the purpose of illustrating the present invention and are not intended to limit the present invention. Based on the examples in this application, all other examples obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] Example 1 To prepare low-phosphorus chemical nickel solution: Nickel sulfate hexahydrate 24g / l, adipic acid 32g / l, sodium hypophosphite 30g / l, LP 8ppm, 74℃, adjust pH to 5.0 with aqueous ammonia.
[0020] Implementation 1: After degreasing and hydrochloric acid activation of the iron-based parts, the parts were placed in the chemical nickel solution, mechanically stirred, and plated for 30 minutes at a plating rate of 22 μm / h to obtain a coating. The coating contained 3.0% phosphorus content measured by an X-ray fluorescence instrument.
[0021] Stability results: Through the supplementary test, the coating phosphorus content reached 3.8% after 15 cycles and a speed of 12 μm / h, which meets the low phosphorus requirements.
[0022] Implementation 2: The flexible polyester cloth that had been pretreated (roughening-washing-activation with an activation solution containing colloidal palladium-washing-degumming-washing) was placed in the chemical nickel solution, mechanically stirred, plated for 8 minutes, and the plating speed was 22 μm / h to obtain a uniform coating. The coating contained 2.9% phosphorus content, the material was soft, and the resistance was measured to be 0.2Ω / in (resistance per inch). The electromagnetic shielding range was between 100K and 3GHz, which met the requirements of electromagnetic shielding materials.
[0023] Stability results: Through the supplementary test, the coating phosphorus content reached 3.5% after 15 cycles and a speed of 12 μm / h, which meets the low phosphorus requirements.
[0024] Example 2 The oxalic acid in Example 1 was replaced with the same amount of malonic acid and succinic acid, and the other conditions were the same as those in Example 2. The phosphorus contents of the obtained coatings were 7.5% and 4.8%, respectively, which did not meet the requirements for low-phosphorus coatings.
[0025] Example 3 Low phosphorus chemical nickel solution: Nickel sulfate hexahydrate 25g / l, sodium adipate 20g / l, glutaric acid 5g / l, boric acid, 10g / l, sodium hypophosphite 24g / l, potassium antimony tartrate 15ppm, LP 15ppm, 76℃, pH 4.8.
[0026] Implementation 1: After degreasing and hydrochloric acid activation of the iron-based parts, put them into the above chemical nickel solution, let them stand for 20 minutes, and obtain a coating with no pinholes on the surface of the coating. The phosphorus content of the coating measured by an X-ray fluorescence instrument is 2.8%.
[0027] Solution stability: The stability test was conducted by injecting palladium chloride solution. There was no decomposition phenomenon for 8 hours, and the stability was extraordinary.
[0028] Embodiment 2: The pre-treated (refer to Example 1) flexible material PET film was placed in the above chemical nickel solution, and plated for 6 minutes to obtain a uniform coating with a thickness of 1.2 μm. The X-ray fluorescence instrument measured the coating with a phosphorus content of 2.6%, the material was soft, the resistance was 0.3Ω / in, and the electromagnetic shielding range was between 100K and 3GHz, which met the requirements of electromagnetic shielding materials.
[0029] Example 4 In Example 3, LP was replaced by the same amount of sulfur-containing compound sodium polydisulfide propane sulfate (SPS) as a copper plating refiner and brightener. According to the method of Example 1, other conditions were the same, and the phosphorus content of the obtained coating was 4.6%, which did not meet the requirements of low-phosphorus coating.
[0030] Example 5 Without adding LP, other conditions were the same as those of Example 3. The phosphorus content of the obtained coating was 4.5%, pinholes were found on the surface of the coating on the parts, and the solution was unstable and decomposed in about 8 minutes.
[0031] Example 6 Nickel chloride hexahydrate 18 g / l, ammonium adipate 40 g / l, sodium hypophosphite 18 g / l, potassium iodate 5 ppm, thiourea 3 ppm, LP 12 ppm, unsaturated organic matter propargyl alcohol glycol ether (PME) 5 ppm, 75°C, pH 4.6.
[0032] Implementation 1: After the copper base parts are degreased and activated with hydrochloric acid, the iron is triggered, air is stirred, and the coating is plated for 30 minutes. The phosphorus content of the coating is 1.7% as measured by an X-ray fluorescence instrument.
[0033] Embodiment 2: The pre-treated (refer to Example 1) flexible polyester cloth was immersed in the above chemical nickel solution, stirred in air, and plated for 10 minutes to obtain a 1.8 μm coating. The phosphorus content of the coating was measured by an X-ray fluorescence instrument to be 1.6%, the material was soft, the resistance was about 0.3 Ω / in, and the electromagnetic shielding range was between 100K and 3 GHz, which met the requirements of electromagnetic shielding materials.
[0034] Example 7 Nickel sulfamate 25 g / l, sodium glutarate 40 g / l, sodium hypophosphite 25 g / l, potassium iodide 2 ppm, LP 20 ppm, bismuth chloride 2 ppm, adjust pH to 4.2, 78°C.
[0035] Implementation: After pretreatment, the flexible polyimide material was immersed in the above chemical nickel solution, stirred in air, and plated for 6 minutes to obtain a 1.8μm coating. The X-ray fluorescence instrument measured that the phosphorus content of the coating was 2.8%, the material was soft, the resistance was about 0.15Ω / in, and the electromagnetic shielding range was between 100K and 3GHz, which met the requirements of electromagnetic shielding materials.
[0036] The present invention is described in detail above in conjunction with the embodiments, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of application of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A low-phosphorus chemical nickel solution, characterized in that The invention comprises the following components: 10-40 g / L of nickel ion source, 5-50 g / L of complexing agent, 5-40 g / L of sodium hypophosphite, and 2-30 ppm of polysulfide compound LP, wherein the complexing agent is one or more of adipic acid, adipic acid salt, glutaric acid, and glutaric acid salt.
2. The low-phosphorus chemical nickel solution according to claim 1, characterized in that: The pH of the low-phosphorus chemical nickel solution is adjusted to 4.0-5.4 for later use.
3. The low-phosphorus chemical nickel solution according to claim 1, characterized in that: The nickel ion source is nickel sulfate, nickel sulfamate or nickel chloride.
4. The low-phosphorus chemical nickel solution according to claim 1, characterized in that: The components of the low-phosphorus chemical nickel solution also include one or more of a buffer, a stabilizer, and a brightener.
5. The low-phosphorus chemical nickel solution according to claim 4, characterized in that: The buffer comprises boric acid; the stabilizer comprises one or more of iodate, iodized salt, antimony compound, thiourea and lead compound; the brightener comprises one or more of water-soluble unsaturated organic matter, bismuth compound and cadmium compound.
6. An application of the low-phosphorus chemical nickel solution according to claim 1, characterized in that: The pretreated substrate is placed in a low-phosphorus chemical nickel solution for chemical plating at a pH of 4.0 to 5.4, the plating temperature is 70 to 80° C., and the phosphorus content of the obtained coating is less than 4%.
7. The use of the low-phosphorus chemical nickel solution according to claim 6, characterized in that: The plating time is 2 to 30 minutes.
8. The use of the low-phosphorus chemical nickel solution according to claim 6, characterized in that: The service life of low-phosphorus chemical nickel solution is more than 15 cycles.
9. The use of the phosphorus chemical nickel solution according to claim 6, characterized in that: The substrate comprises an iron substrate, a copper substrate and a flexible material.
10. The use of the phosphorus chemical nickel solution according to claim 9, characterized in that: The low-phosphorus chemical nickel solution is used for preparing conductive cloth.
Citation Information
Patent Citations
Aluminum alloy surface treatment process
CN118390030A